Pelatihan Pengamanan Data Pribadi di Dalam Luasnya Teknologi Saat Ini Dengan Menggunakan Metode Ceasar Chiper - Sovina, Mutiara; Harahap, Faisal Amir; Syahputra, Eka (LPPM Universitas Potensi Utama, 2022)
In the midst of an ever-increasing state of technological development, the development of intranets, servers, websites, browsers, and search engines, which indicate the need for the development of new broad and strong security to accommodate all of our personal data, both large and small scale, in this highly sophisticated era. like this, there are many tools for sending messages including media such as whatsapp and telegram so we can send messages quickly and vice versa we can receive messages quickly, we can easily send messages so we can send news quickly even though we send it to people who are far away . Of all the conveniences it will certainly be very influential when we are going to send messages whose contents are only certain people who are allowed to know the contents, One thing that must be really guarded is a confidential message because if the message is spread it will have a bad impact on us . One way that is commonly used is encryption. Encryption is the process of disguising the meaning of a message so that unauthorized persons cannot know the meaning of the message. Keywords: Data Security, Technology, Kriptografi, Ceasar Chipher,